Prognostic impact of lepidic growth in intermediate and high-grade lung adenocarcinoma - Niedermaier, Benedikt Walter; Rolf, Erik; Allgäuer, Michael; Klotz, Laura Valentina; Schneider, Marc; Yuskaeva, Kadriya; Eichhorn, Martin E.; Winter, Hauke (Lung cancer, 2025)
Background - Grade 1 lung adenocarcinomas, which are characterized by predominantly lepidic growth and less than 20 % high-risk patterns, have a favorable survival rate compared to higher-grade tumors. However, the prognostic relevance of lepidic components in intermediate and high-grade tumors (grades 2-3) remains unclear. We investigated whether lepidic growth impacts survival in grade 2-3 stage I lung adenocarcinomas. - Methods - 479 consecutive patients who underwent curative resection for non-mucinous lung adenocarcinoma in pathologic grade 2-3 and stage I were enrolled in this retrospective, single-center study. The impact of lepidic components and other predictors on survival was assessed in multivariable cox regression. - Results - Lepidic growth was present in 300 (62.6 %) tumors. Patients with lepidic-positive tumors were significantly older (median age 67 vs. 65 years, p = 0.015), more frequently never-smokers (22.1 % vs. 9.9 %, p = 0.001), had higher proportions of acinar-predominant (69.0 % vs. 53.1 %, p = 0.001), and fewer solid-predominant tumors (7.0 % vs. 26.8 %, p < 0.001). Median follow-up was 67 months (IQR 47-92). Multivariable Cox analysis demonstrated no significant association between lepidic growth and overall or recurrence-free survival. Factors significantly affecting recurrence-free survival included age ≥ 70 years (HR 1.40, p = 0.046), stage IB (HR 1.52, p = 0.017), grade 3 tumors (HR 1.42, p = 0.040), and lymphatic invasion (HR 1.67, p = 0.011). - Conclusion - Lepidic growth did not demonstrate prognostic significance in intermediate and high-grade non-mucinous lung adenocarcinoma in this study.
Gesehen am 10.12.2025